CONTEMPORARY DWELLING PLANNING SCHEMES ANALYSIS (Innovation in Woodworking Industry and Engineering design, 2026)
In the years of rapid construction the building's large scale comes to the fore, shifting the importance from the individual dwelling as a building component unit. The stress is laid on the quantitative rather than on the qualitative aspect of the project, thus neglecting the floor plans; the planning schemes optimization is often at the expense of the individual dwelling size and functionality. The purpose of this work is to analyze the specific dwelling planning schemes in modern residential buildings and to trace the trends in their development.